Pengaruh Penggunaan Agregat Batu Karang Sebagai Pengganti Agregat Halus Terhadap Beton - Elsyanto Pararuk; Frans Phengkarsa; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Development is important to make human life improve and as a reallife support. Quality sturdy buildings are produced from products that are resistant to shocks to make the durability of the building also guaranteed. Concrete is made of materials mixed together, including sand, cement, gravel and aggregate which has a rough texture and smooth texture. In this study, coral was used as an added material in the concrete mixture. The purpose of this study was to determine the effect of using coral aggregate to replace some fine aggregate as a concrete mixture by testing compressive strength, tensile split, and modulus of elasticity with a concrete quality plan of 25 MPa. Based on the results of tests that have been carried out in cylindrical test specimens on several variations of 0%, 35%, 40% and 45% corroboration values of 26.233 MPa, 27.271 MPa, 27.648 MPa and 28.497 MPa, tensile strength values of 2.383 MPa, 2.524 MPa, 2.548 MPa and 2.689 MPa for elasticity modulus obtained values of 23056.250 MPa, 23249.712 MPa, 23518.210 MPa and 23780.946 MPa. From the results of research the use of coral in concrete mixture can affect the strength of concrete, the strength of concrete increases with the variation of rocks added and the strength of concrete will increase with the variation of rocks added.